seasonal variation of blood pressure is not associated with dietary acid load in peritoneal dialysis - Lei Quan; Yanjun Li; Rong Xu; Jie Dong (The Korean Society of Nephrology, 2012)
Seasonal variation of blood pressure is a common phenomenon in dialysis patients. The potential mechanisms are not verified. Whether dietary acid load plays an importance role in seasonal variation of blood pressure is unknown. A total of 181 clinically-stable patients who had been on peritoneal dialysis(PD) more than 3 months were studied between June, 2011 and Nov, 2011, i.e summer to autumn, when seasonal variation of blood pressure represented most obviously. Blood pressure and dietary nutrients intakes were measured monthly and time-averaged values calculated for summer and autumn respectively. Dietary acid load was estimated by NEAP: NEAP (mEq/d)=54.5*protein (g/d)/potassium (mEq/d)-10.2. Other biochemistry and dialysis adequacy was examined also. With the cold season coming, systolic and diastolic blood pressure (SBP and DBP) increased, SBP129.2±16.8mmHg vs 133.9±15.6 mmHG and DBP 76.8±10.5 mmHg vs 78.7±10.1mmHg respectively. Similar trends were observed in body weight, total fluid removal via dialysate and urine, and all dietary nutrients intakes including NEAP values. However, the differences in SBP and DBP between autumn and summer were not associated with the differences in NEAP and dietary nutrients intakes. Conclusions: The increased nutrient intakes including dietary acid load could not explain the seasonal variation of blood pressure in PD patients. Other potential causes still need to be determined.